Development of Rotating Machines on Fractional Materials for Grade III Elementary School Students - Sinta Nurcahyana; Kowiyah Kowiyah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
The purpose of this study was to develop a rotating jentera learning media for class III fractions at SDN Pondok Bahar 05. This research is included in research and development (R & D). This study uses a 4D model with four stages, namely: 1) define stage, 2) design stage, 3) develop stage, 4) disseminate stage. The address of this research is at SDN Pondok Bahar 05. The object of the experiment was carried out by 30 third grade students at the elementary school. This data collection uses a media expert validation questionnaire, a material expert validation questionnaire, and a student response questionnaire. The result of product development is a rotating jentera learning media for fractional materials. The results of the material expert validation got an average score of 80% in the "valid" category. The results of media expert validation obtained an average score of 92.85% with the "very valid" category. The results of student responses based on field trials obtained an average score of 97.92% which included the "very valid" category. Based on the results, it can be concluded that the rotating jentera learning media on fractional material is very suitable to be used as a learning medium for fractional mathematics